Enhancing 21st Century Skills for Prospective Physics Teachers through Arduino-Based Multiple Representations in Learning Heat and Temperature - Siska Desy Fatmaryanti; Eko Setyadi Kurniawan; Yusro Al Hakim; Sarwanto; Desy Luthfianti Ulfah (Jurnal Penelitian Pendidikan IPA, 2024)
There was a gap between traditional teaching and future demands and need a bridge by offering an innovative approach that allows prospective physics teachers to develop key abilities. The main purpose of this study was to improve prospective physics teacher’ 21st century skills in heat and temperature by applying multiple representations learning using Arduino based experiment. The research method used is based on the development procedures of the ADDIE research and development model which includes the stages of analysis, design, development, implementation and evaluation. This study implemented design-based research with a one-group pre-post observation design. The research was conducted on 22 prospective physics teacher students. The teaching materials that have been developed passed the first stage test with a Very Good result. The validity test is assessed by expert validators. The response of students using the teaching materials is Good. In terms of effectiveness, the learning with Arduino based multi representations is able to improve the 21 st -Century Skills with an average N-Gain score of 0.35. Therefore, it can be used by lecture and those in other science fields to improve the quality of learning and developing prospective physics teachers’ 21st Century Skills.